The Yips: Methods to identify golfers with a dystonic etiology/golfer`s cramp - Adler, C. H.; Temkit, M.; Crews, D.; McDaniel, T.; Tucker, J.; Hentz, J. G.; Marquardt, C.; Abraham, D.; Caviness, J. N. (Medicine & Science in Sports & Exercise, 2018)
Purpose To determine whether quantitative methods could separate golfers with a possible dystonic cause of the "yips" from those that appear to be nondystonic.